Thoracoscopic repair of diaphragmatic hernia following ventricular assist device implantation - Ryuta Saka; Takaaki Sakai; Tomomitsu Kanaya; Yuko Tazuke; Yosuke Kugo; Masaki Taira; Takayoshi Ueno; Hiroomi Okuyama (Surgical Case Reports, 2020)
Abstract Background Diaphragmatic hernia is a rare complication of ventricular assist device (VAD), mainly developing after explantation of the device. We herein report a case of diaphragmatic hernia that developed following the implantation of VAD. Case presentation A 4-month-old girl with a diagnosis of dilated cardiomyopathy underwent VAD implantation for a bridge to heart transplantation. Three months later, intermittent vomiting developed, and left-sided diaphragmatic hernia was confirmed on plain X-ray and computed tomography. Without any findings of ischemia, we performed elective thoracoscopic repair of the diaphragmatic hernia. In the right decubitus position, thoracoscopy revealed the small intestine to be herniated into the left thorax. After reduction of the herniated intestine, the defect of the diaphragm (3 × 2 cm in size) was directly closed with interrupted non-absorbable sutures. Her postoperative course was uneventful. Conclusion Thoracoscopic repair of diaphragmatic hernia associated with VAD implantation may be a safe approach.